APOBEC3C S188I Polymorphism Enhances Context-Specific Editing of Hepatitis B Virus Genome . (12th January 2022) - Khalfi, Pierre; Suspène, Rodolphe; Caval, Vincent; Thiers, Valérie; Beauclair, Guillaume; Marchio, Agnès; Bekondi, Claudine; Amougou Atsama, Marie; Camengo-Police, Serge Magloire; Noah Noah, Dominique; Njouom, Richard; Blanc, Hervé; et al.
Abstract: Single-nucleotide polymorphism in APOBEC3C (resulting in a serine to isoleucine in position 188) is present in approximately 10% of African populations and greatly enhances restriction against human immunodeficiency virus-1 and simian immunodeficiency virus by improving dimerization and DNA processivity of the enzyme. In this study, we demonstrated in culture and in infected patients that hepatitis B virus (HBV) could be edited by APOBEC3CS188I . Using next-generation sequencing, we demonstrated that APOBEC3CS188I led to enhanced editing activity in 5ʹTpCpA→5ʹTpTpA context. This constitutes a new hallmark of this enzyme, which could be used to determine its impact on HBV or nuclear DNA. Abstract : In this study, we demonstrated in culture and in patients that HBV could be edited by APOBEC3CS188I . This enzyme led to an enhanced editing activity in a more specific 5ʹTpCpA→5ʹTpTpA context. This constitutes a new hallmark of APOBEC3CS188I .